Cooling and quick-drying business suit fiber fabric and preparation method thereof

CN122980228APending Publication Date: 2026-10-27JIANGSU HUBAO GROUP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611238283.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]上述路线中,共混改性受纤维可纺性与毛型手感的限制;组织结构路线依靠双层结构的亲疏水差异,在精纺西服面料的紧密织物上不易实施;酶法整理以水解鳞片层为主,提高接触凉感的作用有限,并伴随断裂强力下降

Benefits of technology

[0010](1)在钙盐和尿素加入之前先将负载单宁酸的镁铝水滑石粉体吸附于纤维表面,使其部分承担成核调节剂的作用。单宁酸没食子酰基上的邻位酚羟基螯合钙离子,使钙在片层表面富集,碳酸钙优先在纤维表面的片层上成核。在无机相沉积总量相当的条件下,本方法所得面料的接触瞬间最大热流量高于在矿化完成后再加入粉体的面料,也高于以预制碳酸钙和粘合剂涂覆所得的面料。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of textile finishing, and particularly relates to a cool and quick-drying business suit fiber fabric and a preparation method thereof. The method is characterized in that magnesium-aluminum hydrotalcite is reacted with 30-50% tannic acid by mass at pH 5.5-6.5, and the powder loaded with tannic acid is obtained after washing and drying; the worsted wool-polyester blended fabric is wetted with a bath ratio of 1:20 and the powder is added, and the dosage is 1.5-2.5 g / L based on dry basis; then soluble calcium salt and urea are added to make the calcium ion concentration 0.02-0.03 mol / L, and after adjusting the pH to 6-7, urease is added, and the treatment is carried out at 33-37 DEG C until the bath pH rises to 8.1-8.6, and then the enzyme is inactivated, the fabric is washed and shaped. Calcium carbonate is nucleated and grows on the lamella on the surface of the fiber, and the contact cool feeling, quick-drying performance and washing durability of the fabric are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile finishing technology, specifically to a cool-feeling, quick-drying business suit fiber fabric and its preparation method. Background Technology

[0002] Business suits are mostly made of worsted wool or wool-polyester blended woven fabrics, requiring crispness, drape, and good wrinkle recovery. In recent years, requirements for summer and transitional season business attire have emphasized instantaneous cooling against the skin and quick-drying properties during wear, typically evaluated by a combination of maximum heat flow upon contact and dynamic liquid moisture transfer. In the textile finishing field, other bio-based technologies that use enzymes instead of chemical reagents have gained attention due to their milder reaction conditions and fewer byproducts.

[0003] Existing cooling and quick-drying fabrics are mainly obtained through two routes. One is by blending highly thermally conductive inorganic powders during the fiber forming stage. Patent CN113430668B discloses cooling and quick-drying fibers and cooling and quick-drying fabrics made from them. The other is by relying on the fabric structure to form one-way moisture-wicking channels. Patent CN112760793A discloses lightweight quick-drying cooling one-way moisture-wicking knitted fabrics and their production method. Regarding enzymatic finishing of wool fabrics, patent CN105544198B discloses an antibacterial and anti-felting finishing method for wool fabrics, which involves pretreatment with hydrogen peroxide followed by sequential treatment of the scale layer with keratinase and alkaline protease, and then finishing with glyceryl citrate. This document and the present invention belong to the category of bio-enzymatic finishing methods for wool fabrics. The improvements of the present invention are also made at this level, but the problems it solves are different from those of the present invention.

[0004] Of the aforementioned approaches, blending modification is limited by fiber spinnability and wool-like hand feel; the structure-based approach relies on the hydrophilic / hydrophobic difference of the double-layer structure, which is difficult to implement on tightly woven worsted suit fabrics; enzymatic finishing mainly hydrolyzes the scale layer, offering limited improvement in cooling sensation upon contact and accompanied by a decrease in breaking strength. While finishing with hydrophilic agents can improve moisture absorption, these agents adhere through physical deposition and are gradually washed away after repeated washing; furthermore, hydrophilicization acts on both the skin-contact surface and the outer layer, and the moisture and heat conduction conditions required for maintaining a cooling sensation on the skin-contact surface cancel each other out with the rapid dehydration required for quick drying on the same fabric surface. Summary of the Invention

[0005] The technical problem to be solved by this invention is that after the worsted wool-polyester blended suit fabric is made hydrophilic, the moisture and heat conduction conditions required to maintain a cool feeling on the skin surface cancel each other out with the dehydration required for quick drying, and the functional components are attached by physical deposition, making it difficult to withstand multiple washes.

[0006] To solve the above technical problems, the present invention provides a method for preparing a cool-feeling and quick-drying business suit fiber fabric, comprising the following steps: dispersing magnesium aluminum hydrotalcite in water, adding tannic acid, the amount of tannic acid added being 30%~50% of the mass of magnesium aluminum hydrotalcite, maintaining the pH of the system at 5.5~6.5 during the reaction, centrifuging after the reaction, washing with water, and drying to obtain magnesium aluminum hydrotalcite powder loaded with tannic acid; wetting a worsted wool-polyester blended fabric in water, the mass-volume ratio of the fabric to the bath liquid being 1:20, adding the powder obtained in step (1) to the bath, the amount being 1.5~2 on a dry basis. 5g / L, stir treatment; add soluble calcium salt and urea to the same bath in step (2) so that the concentration of calcium ions in the bath is 0.02~0.03mol / L, the molar ratio of urea to calcium ions is 1.5:1, adjust the pH of the bath to 6~7, then add urease to the bath, treat the fabric at 33~37℃ until the pH of the bath rises to 8.1~8.6; the soluble calcium salt is selected from calcium chloride, calcium nitrate and calcium acetate; heat to 85℃ and keep for 15min to deactivate urease, drain the liquid, wash with water, pre-dry the fabric and stretch and shape it to obtain cool and quick-drying business suit fiber fabric.

[0007] Preferably, the magnesium-aluminum hydrotalcite is a carbonate-type layered double hydroxide with a magnesium-aluminum molar ratio of 2:1 and a specific surface area of ​​60-80 m². 2 / g, the average transverse dimension of the flakes is 1~2μm; in step (1), the reaction is carried out at 40℃ for 4h, and the organic content of the obtained powder is 14%~22%; in step (2), the wool to polyester fiber blend ratio of the worsted wool-polyester blended fabric is 55 / 45, and the areal density is 220g / m 2 In addition, a sodium polyaspartate aqueous solution with a solid content of 40% or less at a concentration of 0.45 g / L is added to the bath; the amount of urease added in step (3) is 180~300 U / L based on enzyme activity, and the treatment time is 120~180 min.

[0008] The present invention also provides a cool-feeling and quick-drying business suit fiber fabric prepared by the above preparation method.

[0009] The beneficial effects of this invention are as follows:

[0010] (1) Before adding calcium salts and urea, magnesium aluminum hydrotalcite powder loaded with tannic acid is adsorbed onto the fiber surface, allowing it to partially act as a nucleation regulator. The ortho-phenolic hydroxyl groups on the galloyl group of tannic acid chelate calcium ions, enriching calcium on the surface of the lamellae, and calcium carbonate preferentially nucleates on the lamellae of the fiber surface. Under the condition of equivalent total inorganic phase deposition, the maximum instantaneous heat flux of the fabric obtained by this method is higher than that of the fabric with powder added after mineralization, and also higher than that of the fabric obtained by coating with pre-prepared calcium carbonate and adhesive.

[0011] (2) Step (1) under acidic conditions, tannic acid is loaded onto the surface of the magnesium aluminum hydrotalcite plate and the free tannic acid is washed away, so that the surface of the plate has sites for chelating calcium ions, and the free tannic acid in the bulk solution no longer competes for calcium ions, thereby improving the adhesion and retention of the plate on the fiber surface and increasing the maximum heat flow at the moment of contact.

[0012] (3) Urease catalyzes the hydrolysis of urea, causing a slow increase in carbonate concentration and alkalinity. The supersaturation reaches a critical level first in the calcium-rich region on the surface of the sheets. Calcium carbonate grows on the fiber surface via heterogeneous nucleation and intergranular aggregation, forming a microcrystalline shell that retains submicron pores. Compared to directly adding carbonates, the total amount of inorganic phase deposition is increased; compared to pre-prepared calcium carbonate with adhesive coating, a continuous adhesive film with closed pores is not formed. Therefore, when the total amount of inorganic phase deposition is comparable, the fabric's air permeability and dynamic liquid moisture transfer properties are maintained. Other bio-technical routes that use enzyme preparations instead of chemical reagents can be completed in a room-temperature aqueous phase.

[0013] (4) The powder is adsorbed on the fiber surface before the calcium salt is added. The growing calcium carbonate then fixes the lamellars on the yarn surface, preventing the inorganic phase from entering the yarn core. Compared with adding the powder after mineralization and washing, the decrease in the combined quick-drying properties of the maximum heat flow at contact and the dynamic transfer of liquid moisture is reduced after 20 washes using a household washing program.

[0014] (5) The amount of powder used should be controlled at 1.5~2.5g / L, and the substitution range can be adjusted by using sodium polyaspartate. When the amount is below this range, the layer coverage is insufficient, the nucleation sites are sparse, and the maximum heat flow at the moment of contact does not reach the value for judging the cooling sensation; when the amount is above this range, the layers are stacked on the fiber surface, the moisture transfer channels are blocked, and the fabric feels stiff. Within this range, the cooling sensation, wrinkle recovery, and breathability are balanced; this treatment does not hydrolyze the wool scale layer and the polyester fiber body, and the tensile strength of the fabric is comparable to that of the fabric treated only with hydrophilic finishing. This is especially important for other bio-enzymatic finishing routes, because the finishing route of hydrolyzing the scale layer with protease will significantly reduce the tensile strength. Detailed Implementation

[0015] The present invention will be further described below with reference to preparation examples, embodiments, and comparative examples.

[0016] The worsted wool-polyester blended fabrics used in the preparation examples, embodiments, and comparative examples were sourced from Jiangsu Sunshine Group Co., Ltd., and were wool to polyester blended in a 55 / 45 ratio with an areal density of 220 g / m². 2 The fabric is a 2 / 2 twill semi-bleached fabric; the magnesium-aluminum hydrotalcite is sourced from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., and is a flower-shaped magnesium-aluminum hydrotalcite with a magnesium-aluminum molar ratio of approximately 2:1. The interlayer anion is carbonate, and the specific surface area is 60~80m². 2 / g, the average lateral size of the lamellar layers is 1~2μm, and the interlayer spacing of the (003) crystal planes is 0.76~0.78nm; the tannic acid is from Changsha Shanghe Biotechnology Co., Ltd., is food grade, and has a molecular weight of 1434~1701; the urease is an enzyme preparation derived from sword bean, with the product number Sigma-Aldrich. 94280, nominal activity approximately 1 U / mg; Sodium polyaspartate is from Zibo Runju Biotechnology Co., Ltd., is an aqueous solution with a solid content of 40%; Polyether-modified silicone hydrophilic softener is from Shanghai Chuyijia Silicone Materials Co., Ltd., is a nonionic water-soluble polyether-modified silicone oil with a solid content of 100%; Anhydrous calcium chloride, urea, sodium carbonate and 30% hydrogen peroxide aqueous solution are from Sinopharm Chemical Reagent Co., Ltd., all are analytical grade; Light calcium carbonate is from Sinopharm Chemical Reagent Co., Ltd., with an average particle size of 2~3μm; Polyacrylate emulsion binder is a nonionic self-crosslinking variety for textile coating, with a solid content of 45%; Glyceryl citrate is a general-purpose variety for textile finishing; Keratinase has a nominal activity of 20000 U / g, and alkaline protease has a nominal activity of 50000 U / g.

[0017] All fabric wet treatments in the embodiments and comparative examples were carried out in a 2L capacity laboratory overflow sampler. The fabric was circulated in the bath at a flow rate of 3L / min. This circulation was maintained throughout the pre-adsorption, feeding, heat preservation, and enzyme inactivation processes. The bath temperature was controlled by a jacket at a heating rate of 2℃ / min. Tensile setting was performed on a laboratory setting machine with a setting width of 100% of the greige fabric width and an overfeed rate of 2%.

[0018] Preparation Example 1: Magnesium aluminum hydrotalcite powder loaded with tannic acid

[0019] Weigh 20g of magnesium aluminum hydrotalcite and add 800mL of deionized water. Stir at 800r / min for 30min at room temperature to obtain a hydrotalcite dispersion. Separately weigh 8g of tannic acid and dissolve it in 200mL of deionized water to obtain a tannic acid aqueous solution. Add the tannic acid aqueous solution to the hydrotalcite dispersion at a uniform rate over 20min while stirring. Adjust the pH of the system to 6 with 0.1mol / L hydrochloric acid and continue stirring at 40℃ for 4h. Magnesium aluminum hydrotalcite is an acid-consuming solid, and the pH will rise over time during the reaction. Continuously monitor the pH with a pH meter and add 0.1mol / L hydrochloric acid to maintain the pH of the system between 5.5 and 6.5 throughout the process. The standard for determining the pH is that the reading does not drift by more than 0.1 within 5min. Centrifuge the resulting slurry at 4000r / min for 10min, discard the supernatant, and redisperse the mixture with 500mL of deionized water each time. Repeat this washing process three times. The standard for determining cleanliness is that the washing liquid does not turn blue after testing with Folin-Ciocalteu reagent. The precipitate was dried at 60℃ and a vacuum degree not exceeding 10 kPa for 8 hours to constant weight, then ground through a 200-mesh sieve to obtain 23.4 g of magnesium aluminum hydrotalcite powder loaded with tannic acid. The moisture content was measured to be no more than 1% after drying at 105℃ to constant weight; all subsequent dosages were based on this dry basis. Three batches were prepared in parallel under the same conditions, with yields of 23.1 g, 23.8 g, and 23.3 g, respectively. These were combined and mixed before being used in the examples and comparative examples.

[0020] The powder was calcined at 500℃ for 2 hours, and the residual rate was measured to be 45.7%. Magnesium aluminum hydrotalcite without tannic acid loading was calcined in the same way, and the residual rate was measured to be 56%. According to the formula of organic content = (1−45.7% / 56%)×100%, the organic content of the powder is 18.4%.

[0021] Preparation Example 2: Magnesium Aluminum Hydrotalcite Powder Loaded with Tannic Acid

[0022] Except for changing the amount of tannic acid added to 6g, the other raw materials, amounts and preparation conditions were the same as in Preparation Example 1, and 22.3g of magnesium aluminum hydrotalcite powder loaded with tannic acid was obtained. Its organic content was measured to be 14.5% by the same method.

[0023] Preparation Example 3: Magnesium Aluminum Hydrotalcite Powder Loaded with Tannic Acid

[0024] Except for changing the amount of tannic acid added to 10g, the other raw materials, amounts and preparation conditions were the same as in Preparation Example 1, and 24.4g of magnesium aluminum hydrotalcite powder loaded with tannic acid was obtained. Its organic content was measured to be 21.9% by the same method.

[0025] Example 1:

[0026] Step (1): Take 50g of worsted wool-polyester blended fabric, add 1000mL of deionized water, and soak at 40℃ for 10min to fully wet the fabric.

[0027] Step (2): Add 1.50 g of the powder obtained in Preparation Example 1 and 0.45 g of sodium polyaspartate aqueous solution to the bath and circulate it at 40 °C for 30 min.

[0028] Step (3): Add 2.22g of anhydrous calcium chloride and 1.80g of urea to the same bath in sequence and stir until completely dissolved; at this time the pH of the bath solution is 8.2, adjust it to 6.5 with 0.1mol / L hydrochloric acid, and then lower the bath temperature to 35℃.

[0029] Step (4): Add 0.20g of urease and keep warm at 35℃ for 120min; the pH of the bath solution increases from 6.5 to 8.3, the bath solution becomes slightly turbid, and the fabric surface changes from smooth to uniform matte.

[0030] Step (5): Leave the fabric in the bath, raise the temperature to 85℃ at 2℃ / min and keep it for 15min to deactivate urease, drain the liquid, wash twice with 1000mL of 50℃ deionized water, and then wash once with room temperature deionized water.

[0031] Step (6): Pre-dry the fabric at 80℃ for 5 minutes until there are no obvious water stains, and then stretch and fix it at 150℃ for 60 seconds to obtain cool and quick-drying business suit fiber fabric.

[0032] Example 2:

[0033] Step (1): Take 50g of worsted wool-polyester blended fabric, add 1000mL of deionized water, and soak at 40℃ for 10min to fully wet the fabric.

[0034] Step (2): Add 2.40 g of the powder obtained in Preparation Example 1 to the bath and circulate it at 40 °C for 30 min.

[0035] Step (3): Add 2.22g of anhydrous calcium chloride and 1.80g of urea to the same bath in sequence and stir until completely dissolved; at this time the pH of the bath solution is 8.2, adjust it to 6.5 with 0.1mol / L hydrochloric acid, and then lower the bath temperature to 35℃.

[0036] Step (4): Add 0.20g of urease and keep warm at 35℃ for 120min; the pH of the bath solution increases from 6.5 to 8.3, the bath solution becomes slightly turbid, and the fabric surface changes from smooth to uniform matte.

[0037] Step (5): Leave the fabric in the bath, raise the temperature to 85℃ at 2℃ / min and keep it for 15min to deactivate urease, drain the liquid, wash twice with 1000mL of 50℃ deionized water, and then wash once with room temperature deionized water.

[0038] Step (6): Pre-dry the fabric at 80℃ for 5 minutes until there are no obvious water stains, and then stretch and fix it at 150℃ for 60 seconds to obtain cool and quick-drying business suit fiber fabric.

[0039] Example 3:

[0040] Step (1): Take 50g of worsted wool-polyester blended fabric, add 1000mL of deionized water, and soak at 40℃ for 10min to fully wet the fabric.

[0041] Step (2): Add 1.50 g of the powder obtained in Preparation Example 1 and 0.45 g of sodium polyaspartate aqueous solution to the bath and circulate it at 40 °C for 30 min.

[0042] Step (3): Add 3.33g of anhydrous calcium chloride and 2.70g of urea to the same bath in sequence and stir until completely dissolved; at this time the pH of the bath solution is 8.2, adjust it to 6.5 with 0.1mol / L hydrochloric acid, and then lower the bath temperature to 35℃.

[0043] Step (4): Add 0.30g of urease and keep warm at 35℃ for 120min; the pH of the bath solution increases from 6.5 to 8.1, the bath solution becomes obviously turbid, and the fabric surface changes from smooth to uniform matte.

[0044] Step (5): Leave the fabric in the bath, raise the temperature to 85℃ at 2℃ / min and keep it for 15min to deactivate urease, drain the liquid, wash twice with 1000mL of 50℃ deionized water, and then wash once with room temperature deionized water.

[0045] Step (6): Pre-dry the fabric at 80℃ for 5 minutes until there are no obvious water stains, and then stretch and fix it at 150℃ for 60 seconds to obtain cool and quick-drying business suit fiber fabric.

[0046] Comparative Example 1:

[0047] Step (1): Take 50g of worsted wool-polyester blended fabric, add 1000mL of deionized water, 20g of 30% hydrogen peroxide aqueous solution and 0.2g of sodium hydroxide, adjust the pH to 8, treat at 30℃ for 25min, and then raise the temperature to 50℃.

[0048] Step (2): Add 0.15g of keratinase and treat at pH 8 and 50℃ for 20min; then add 0.10g of alkaline protease and treat at 60℃ for 10min. After draining, wash with water until neutral.

[0049] Step (3): The fabric is dipped and rubbed twice in 1000mL of aqueous solution containing 25g of glyceryl citrate at 70℃, with a 70% rub-off rate. After treatment for 10min, it is thoroughly washed with water.

[0050] Step (4): Dry the fabric at 80°C to obtain the fabric material.

[0051] Comparative Example 2:

[0052] Step (1): Take 50g of worsted wool-polyester blended fabric and dip and nibble it twice in 1000mL of aqueous solution containing 20g of polyether-modified silicone hydrophilic softener, with a pick-up rate of 70%.

[0053] Step (2): Pre-dry the fabric at 80℃ for 5 minutes, and then stretch and set it at 150℃ for 60 seconds to obtain the fabric.

[0054] Comparative Example 3:

[0055] Except for replacing 1.50g of magnesium aluminum hydrotalcite with the powder obtained in Example 1, the other raw materials, amounts and preparation conditions were the same as in Example 1, and the fabric was obtained.

[0056] Comparative Example 4:

[0057] Except for replacing 1.50g of the powder obtained in Example 1 with 1.22g of magnesium aluminum hydrotalcite and 0.28g of tannic acid respectively, the other raw materials, dosages and preparation conditions were the same as in Example 1, and the fabric was obtained.

[0058] Comparative Example 5:

[0059] Except for the absence of the powder obtained in Preparation Example 1 in step (2), the other raw materials, amounts, and preparation conditions are the same as in Example 1. Due to this change, after enzyme inactivation, draining, and washing, 1.50 g of the powder is added to 1000 mL of deionized water and stirred at 800 r / min for 20 min to prepare a dispersion. The fabric is then immersed in the dispersion and immersed in it at 40°C at a circulation rate of 3 L / min for 30 min. After draining, it is pre-dried and shaped to obtain the fabric.

[0060] Comparative Example 6:

[0061] Except for not adding the powder obtained in Preparation Example 1 and changing the amount of sodium polyaspartate aqueous solution added to 1.50g, the other raw materials, amounts and preparation conditions were the same as in Example 1, and the fabric was obtained.

[0062] Comparative Example 7:

[0063] Except for the absence of urea and urease, the other raw materials, dosages, and preparation conditions were the same as in Example 1. Due to this change, after pre-adsorption, 100 mL of deionized water containing 2.12 g of sodium carbonate was pumped into the liquid below the surface at a constant rate of 3 L / min within 5 min using a peristaltic pump. The mixture was then circulated at 35°C for 120 min, followed by direct drainage and washing in the same manner to obtain the fabric.

[0064] Comparative Example 8:

[0065] Step (1): Add 34g of light calcium carbonate and 40g of polyacrylate emulsion binder to deionized water to prepare a slurry with a total volume of 1000mL, and stir at 800r / min for 20min.

[0066] Step (2): Take 50g of worsted wool-polyester blended fabric, dip and nibble it twice in the above slurry, with a pick-up rate of 75%.

[0067] Step (3): Pre-dry the fabric at 80℃ for 5 minutes, and then bake it at 150℃ for 90 seconds to obtain the fabric.

[0068] Comparative Example 9:

[0069] Except for changing the amount of powder added in Preparation Example 1 to 0.20g, the other raw materials, amounts and preparation conditions were the same as in Example 1, and the fabric was obtained.

[0070] Comparative Example 10:

[0071] Except for changing the amount of powder added to 4g in Example 1, the other raw materials, amounts and preparation conditions were the same as in Example 1, and the fabric was obtained.

[0072] Comparative Example 11:

[0073] Except for changing the amount of powder added in Preparation Example 1 to 0.60g and the amount of sodium polyaspartate aqueous solution added to 0.90g, the other raw materials, amounts and preparation conditions were the same as in Example 1, and the fabric was obtained.

[0074] Comparative Example 12:

[0075] Except for changing the amount of anhydrous calcium chloride to 1.11g and the amount of urea to 0.90g, the other raw materials, dosages and preparation conditions are the same as in Example 1; the pH of the bath solution in this example is increased from 6.5 to 8.5 to obtain the fabric.

[0076] Performance testing:

[0077] Each sample was prepared in 3 batches independently. The number of samples in each batch was measured according to the standard, and the average value within the batch was taken first. Then, the arithmetic mean of the 3 batches was taken. The table shows the average value of the 3 batches.

[0078] 1. Instantaneous cooling sensation upon contact: The maximum instantaneous heat flux qmax was determined according to GB / T 35263-2017 "Test and evaluation of instantaneous cooling sensation performance of textiles". After conditioning the sample according to GB / T 6529, the sample was placed with the side closest to the body during wear facing upwards. The temperature of the sample stage was (20±0.5)℃, the temperature of the thermal testing plate was (35±0.5)℃, and the contact pressure was (0.1±0.01) N / cm². 2Five 200mm × 200mm samples were taken from each batch. The standard specifies that qmax should not be less than 0.15 J / (cm²). 2 •s) Determine if the sample has a cooling sensation upon contact. Single measurement values ​​are retained to three decimal places; for ease of comparison between groups, Table 1 lists the arithmetic mean of three batches that are not rounded according to this standard.

[0079] 2. Dynamic Moisture Transfer: According to GB / T 21655.2-2019 "Evaluation of Moisture Absorption and Quick-Drying Properties of Textiles - Part 2: Dynamic Moisture Transfer Method", the immersion time, water absorption rate, maximum immersion radius, liquid water diffusion rate, and unidirectional moisture transfer index were collected. Five samples were taken from each batch, with the side closest to the body during wear considered the immersion surface. The comprehensive index obtained by the instrumental weighted calculation of the above five items is denoted as OMMC, dimensionless, and ranges from 0 to 1. A higher value indicates better overall quick-drying performance.

[0080] 3. Performance after washing: Wash according to the 4N procedure of GB / T 8629-2017 "Test Procedures for Household Washing and Drying of Textiles", using standard detergent No. 1 of the standard, with a total washing load of (2±0.1) kg and a test water hardness of less than 0.7 mmol / L; hang to dry according to procedure A after each wash, and repeat this washing and drying process 20 times. After the last drying, readjust the humidity according to GB / T 6529, and then retest qmax and OMMC according to the above method.

[0081] 4. Wrinkle recovery: The test was conducted according to the horizontal method in GB / T 3819-1997 "Determination of wrinkle recovery of textiles - Recovery angle method". The pressure load was 10N, the pressure time was (5±0.05)min, and the reading was taken 5min after the pressure was released. Ten samples were taken in the warp and ten in the weft directions, including five samples folded in half from the front and five samples folded in half from the back. The result was expressed as the sum of the recovery angles in the warp and weft directions and rounded to 1°.

[0082] 5. Air permeability: Tested according to GB / T 5453-1997 "Textiles - Determination of Air Permeability of Fabrics", with a sample area of ​​20 cm². 2 The pressure difference was 100 Pa, and measurements were taken 10 times at different locations on the sample. This standard has been replaced by GB / T 5453-2025, and the replacement version will be implemented from March 1, 2027.

[0083] 6. Breaking strength: The warp breaking strength shall be determined in accordance with GB / T 3923.1-2013 "Textiles - Tensile properties of fabrics - Part 1: Determination of breaking strength and elongation at break (strip method)". Five samples shall be taken from each batch, and the results shall be rounded to 10N according to the grading provisions of the standard.

[0084] 7. Residual Increment on Ignition: Take approximately 2g of fabric samples before and after treatment, dry them to constant weight at 105℃ and weigh them. Place them in a crucible that has been pre-weighed at 500℃, heat to 500℃ at a rate of 5℃ / min and hold for 4 hours to constant weight. Cool to room temperature in a desiccator and weigh them. The balance sensitivity is 0.1mg. The residual ignition rate is obtained by comparing the residual ignition mass of each sample with its dried mass. The difference between the residual ignition rate after treatment and before treatment is the residual increment on ignition. Samples before and after treatment are taken from adjacent parts of the same piece of fabric. This residue contains a composite oxide of calcium carbonate and magnesium aluminum hydrotalcite after ignition. This index characterizes the relative increase in the total amount of inorganic phase on the fiber surface, and does not solely characterize the amount of calcium carbonate deposited.

[0085] 8. Layered Burn Residual Increment: The treated fabric was disassembled into yarns. First, 30% of the outer layer fibers (by weight) were removed, then the middle 40% were removed, leaving the remaining 30% of the core fibers. Each sample was combined and weighed approximately 2g. The burn residual rate was determined using the same method as in section 7. The untreated greige fabric was also measured layer by layer using the same method as a control. The difference between the two samples represents the burn residual increment of the yarn surface and the burn residual increment of the yarn core. These two samples, taken from the outer and core layers of the yarn respectively, do not constitute a complete division of the yarn and are not weighted by mass.

[0086] Table 1. Cooling and quick-drying properties of the fabrics obtained in each embodiment and comparative example.

[0087] Example 1 0.165 0.52 0.157 0.44 Example 2 0.172 0.49 0.164 0.41 Example 3 0.178 0.47 0.170 0.39 Comparative Example 1 0.121 0.38 0.116 0.21 Comparative Example 2 0.115 0.28 0.108 0.13 Comparative Example 3 0.138 0.41 0.124 0.29 Comparative Example 4 0.147 0.44 0.133 0.32 Comparative Example 5 0.143 0.40 0.121 0.24 Comparative Example 6 0.129 0.37 0.122 0.28 Comparative Example 7 0.126 0.34 0.117 0.23 Comparative Example 8 0.152 0.24 0.141 0.20 Comparative Example 9 0.127 0.36 0.119 0.26 Comparative Example 10 0.176 0.38 0.166 0.31 Comparative Example 11 0.142 0.43 0.134 0.35 Comparative Example 12 0.139 0.46 0.132 0.38

[0088] Table 2. Wearing performance of fabrics obtained in each embodiment and comparative example.

[0089] Example 1 271 168.4 620 Example 2 263 155.1 610 Example 3 259 149.6 610 Comparative Example 1 268 182.3 560 Comparative Example 2 275 180.6 620 Comparative Example 3 272 172.4 620 Comparative Example 4 271 170.8 620 Comparative Example 5 270 171.5 620 Comparative Example 6 273 174.7 620 Comparative Example 7 273 173.9 620 Comparative Example 8 252 118.2 620 Comparative Example 9 275 177.1 620 Comparative Example 10 244 132.4 610 Comparative Example 11 274 175.3 620 Comparative Example 12 274 176.2 620

[0090] Table 3. Residual scorch increment of fabrics obtained in each embodiment and comparative example.

[0091] Example 1 2.50 Example 2 3.12 Example 3 3.58 Comparative Example 1 0.12 Comparative Example 2 0.42 Comparative Example 3 1.93 Comparative Example 4 2.14 Comparative Example 5 2.41 Comparative Example 6 1.62 Comparative Example 7 1.18 Comparative Example 8 2.53 Comparative Example 9 1.60 Comparative Example 10 3.92 Comparative Example 11 1.81 Comparative Example 12 1.47

[0092] Table 4. Residual scorch increments in the surface and core of some sample yarns.

[0093] Example 1 4.12 0.81 Comparative Example 5 2.98 1.63 Comparative Example 8 5.76 0.38

[0094] Results Analysis

[0095] As shown in Table 1, the qmax of Examples 1 to 3 is 0.165~0.178 J / (cm³). 2 The concentrations of ·s are not lower than 0.15 J / (cm³) as specified in GB / T35263-2017. 2 The OMMC was 0.47~0.52; the qmax of Comparative Example 2, which underwent conventional hydrophilic treatment, was 0.115 J / (cm). 2The OMMC of Example 1 was 0.28. After 20 washes, the OMMC of Example 1 remained at 0.44, while that of Comparative Example 2 decreased to 0.13. This indicates that the in-situ formation of a calcium carbonate anchoring layer on the fiber surface improves the instantaneous cooling sensation and dynamic liquid moisture transfer performance, and extends the functional wash durability.

[0096] As shown in Tables 1 and 2, the qmax of Comparative Example 1, which was treated with keratinase and alkaline protease followed by citrate glyceryl ester finishing, was 0.121 J / (cm²). 2 After 20 washes, the OMMC of the [specific group name] was 0.21, and the breaking strength was 560N, lower than the above 610N of the other groups. This indicates that the finishing route based on protease hydrolysis of wool scales has limited effect on improving the cooling sensation and is accompanied by a decrease in fiber breaking strength.

[0097] As shown in Tables 1 and 3, Comparative Example 6, which uses sodium polyaspartate without adding powder but with the conventional dosage, has a residual ignition gain of 1.62% and a qmax of 0.129 J / (cm³). 2 ·s); Comparative Example 3, using magnesium aluminum hydrotalcite without tannic acid loading, showed an increase in residual ignition increment of 1.93% and a qmax of 0.138 J / (cm). 2 •s); The residual increase on ignition in Example 1 was 2.50%, and qmax reached 0.165 J / (cm). 2 This indicates that the loading of tannic acid on the surface of the hydrotalcite layer improves the adhesion and retention of the lamellars on the fiber surface, increases the total amount of inorganic phase deposition on the fiber surface, and enhances the instantaneous cooling sensation upon contact. Comparative Example 4 added equal amounts of magnesium aluminum hydrotalcite and tannic acid to a mineralization bath, resulting in a residual ignition increment of 2.14% and a qmax of 0.147 J / (cm³). 2 The concentration of tannic acid (·s) falls between that of Comparative Example 3 and Example 1, indicating that only a portion of the tannic acid is coordinated to the plate during co-addition in the bath, while the remainder remains in the bulk solution to compete for calcium ions. The washing step serves to remove this portion.

[0098] As shown in Tables 1 and 3, Comparative Example 7, which directly added sodium carbonate without using urea and urease, had the same powder dosage and calcium input as Example 1, but its residual increase on ignition was only 1.18%, and qmax was 0.126 J / (cm³). 2 The OMMC was 0.34. The only difference between the two samples was the method of carbonate supply, which allowed the amount of calcium carbonate deposition to be separated: when urease catalyzes the slow establishment of supersaturation through urea hydrolysis, calcium carbonate preferentially nucleates on the fiber surface; when carbonate is added directly, the supersaturation rises too quickly, and calcium carbonate mainly precipitates in the bulk solution.

[0099] As shown in Tables 1 and 4, in Comparative Example 5, after mineralization and washing, the powder was added via impregnation. The residual ignition increment was 2.41%, similar to Example 1. However, after 20 washes, the qmax decreased to 0.121 J / (cm³). 2 The ·s) and OMMC decreased to 0.24; the scorch residue increments of the yarn surface and core were 2.98% and 1.63%, respectively, which are close to those of Example 1, while they were 4.12% and 0.81%. This indicates that the pre-adsorbed powder before the addition of calcium salts fixes the lamellars on the yarn surface, and the inorganic phase is no longer distributed to the yarn core, thereby improving the functional washability.

[0100] As shown in Tables 1, 2, and 4, Comparative Example 8, coated with pre-made calcium carbonate and adhesive, had a residual ignition increment of 2.53%, comparable to Example 1. The residual ignition increment of the yarn surface was 5.76%, and that of the core was 0.38%, indicating a higher enrichment level on the surface than Example 1. However, its OMMC was only 0.24, resulting in a reduced air permeability of 118.2 mm / s and a wrinkle recovery angle of 252°. This suggests that the concentration of inorganic phase on the yarn surface itself is insufficient to provide a cooling sensation and quick-drying properties. The adhesive film coats the grains and fills the micro-bumps on the fabric surface. The polymer film in contact with the skin has a thermal conductivity similar to wool. Simultaneously, the continuous film seals the fabric pores, blocking the lateral spread of moisture. The in-situ nucleated crystal layer does not use an adhesive; the intergranular growth preserves pores, improving the cooling sensation while maintaining air permeability and liquid moisture transfer performance.

[0101] As shown in Tables 1 and 2, compared with Example 1 (both with 0.45 g of sodium polyaspartate added), when the powder dosage is 0.20 g (Comparative Example 9), the qmax is 0.127 J / (cm²). 2 When the powder dosage is 4g (Comparative Example 10), the qmax is 0.176J / (cm³). 2 However, OMMC dropped to 0.38, air permeability dropped to 132.4 mm / s, and wrinkle recovery angle dropped to 244°. This indicates that when the dosage is too low, the sheet layer does not cover the fiber surface sufficiently and the nucleation sites are sparse; when the dosage is too high, the sheet layer stacks on the fiber surface, blocking the moisture transfer channels and making the fabric feel stiff.

[0102] Table 1 shows that the powder dosage of Comparative Example 11 was 0.60 g, and the calcium ion concentration of Comparative Example 12 was 0.01 mol / L. Their qmax values ​​were 0.142 J / (cm²). 2 ·s) and 0.139J / (cm 2 The concentration of J / (cm³) further decreased to 0.134 J / (cm³) after 20 washes. 2 ·s) and 0.132J / (cm 2The concentrations (·s) are all lower than the 0.15 J / (cm³) specified in GB / T 35263-2017. 2 This indicates that when the powder dosage is less than 1.5 g / L or the calcium ion concentration is less than 0.02 mol / L, the resulting fabric will not meet the requirements for instantaneous cooling upon contact.

[0103] As shown in Tables 1 and 2, with increasing calcium ion concentration, the qmax of Comparative Example 12, Example 1, and Example 3 is 0.139 J / (cm³). 2 ·s), 0.165J / (cm) 2 ·s) and 0.178J / (cm 2 The air permeability was 176.2 mm / s, 168.4 mm / s, and 149.6 mm / s, respectively, and the wrinkle recovery angle was 274°, 271°, and 259°, respectively. This indicates that increasing the mineralization amount can further improve the instantaneous cooling sensation upon contact, but at the same time reduces air permeability and wrinkle recovery. The breaking strength of each embodiment was 610~620 N, which is comparable to 620 N of Comparative Example 2, which only underwent hydrophilic finishing, indicating that the treatment process does not hydrolyze the wool scale layer and the polyester fiber body.

Claims

1. A method for preparing a cool-feeling, quick-drying business suit fiber fabric, characterized in that, Includes the following steps: (1) Disperse magnesium aluminum hydrotalcite in water, add tannic acid, the amount of tannic acid added is 30%~50% of the mass of magnesium aluminum hydrotalcite, maintain the pH of the system at 5.5~6.5 during the reaction, centrifuge after reaction, wash with water, dry, and obtain magnesium aluminum hydrotalcite powder loaded with tannic acid. (2) Wet the worsted wool-polyester blended fabric in water, with the mass-to-volume ratio of the fabric to the bath liquid being 1:

20. Add the powder obtained in step (1) to the bath, with the amount being 1.5~2.5 g / L on a dry basis, and stir. (3) Add soluble calcium salt and urea to the same bath as in step (2) to make the concentration of calcium ions in the bath solution 0.02~0.03mol / L, the molar ratio of urea to calcium ions 1.5:1, adjust the pH of the bath solution to 6~7, then add urease to the bath solution, and treat the fabric at 33~37℃ until the pH of the bath solution rises to 8.1~8.6; the soluble calcium salt is selected from calcium chloride, calcium nitrate and calcium acetate; (4) Heat to 85℃ and hold for 15 minutes to deactivate urease, drain, wash with water, pre-dry the fabric and stretch it to obtain cool-feeling quick-drying business suit fiber fabric.

2. The preparation method according to claim 1, characterized in that, The magnesium-aluminum hydrotalcite is a carbonate-type layered double hydroxide with a magnesium-aluminum molar ratio of 2:1 and a specific surface area of ​​60-80 m². 2 / g, with an average transverse dimension of 1~2μm for the sheets.

3. The preparation method according to claim 1, characterized in that, In step (1), the reaction is carried out at 40°C for 4 hours.

4. The preparation method according to claim 1, characterized in that, The organic content of the powder obtained in step (1) is 14%~22%; the organic content is calculated by the following formula: organic content = (1−W1 / W0)×100%, where W1 is the residual rate of the powder after calcination at 500℃ for 2h, and W0 is the residual rate of magnesium aluminum hydrotalcite without tannic acid after calcination in the same way.

5. The preparation method according to claim 1, characterized in that, In step (2), the wool-polyester blended fabric has a wool / polyester fiber blending ratio of 55 / 45 and an areal density of 220 g / m². 2 .

6. The preparation method according to claim 1, characterized in that, In step (2), a sodium polyaspartate aqueous solution with a solid content of 40% is also added, and the amount added is less than 0.45 g / L.

7. The preparation method according to claim 1, characterized in that, The amount of urease added in step (3) is 180~300 U / L, calculated by enzyme activity.

8. The preparation method according to claim 1, characterized in that, The processing time in step (3) is 120~180 min.

9. A cool-feeling, quick-drying business suit fiber fabric, characterized in that, It is prepared by any one of claims 1 to 8.

Citation Information

Patent Citations

  • A kind of antibacterial and anti-felt shrinkage finishing method of wool fabric

    CN105544198B

  • Light-weight quick-dry cool one-way moisture-conducting knitted fabric and production method thereof

    CN112760793A

  • Ice-feel quick-drying fibers and their preparation methods, ice-feel quick-drying fabrics and their preparation methods

    CN113430668B